The Impact Of Percutaneous Coronary Intervention On Echocardiographic Parameters In Patients With Chronic Total Occlusion Of The Coronary Arteries With Diverse Left Ventricular Ejection Fraction (Journal of Medical & Health Sciences Review, 2024)
Background: Chronic total occlusion (CTO) is a problematic group of coronary artery diseases that is commonly linked to impaired myocardial perfusion and left ventricular dysfunction. Percutaneous coronary intervention (PCI) has also become an efficient revascularization approach that could have cardiac remodeling and echocardiographic outcomes.Objective: To assess the effect of PCI on echocardiographic parameters in CTO patients with different baseline left ventricular ejection fractions.Methods: This retrospective study was a single-center, cross-sectional study that was carried out at the Armed Forces Institute of Cardiology (AFIC), Rawalpindi, from July, 2024 to November, 2024. One hundred and twenty patients who had angiographically proven CTO and underwent successful PCI were involved. The pre- and post-intervention parameters measured by echocardiography were left ventricular ejection fraction (LVEF), left ventricular end-diastolic volume (LVEDV), and end-systolic volume (LVESV). Functional improvement was determined by statistical comparison.Results: The echocardiographic assessment at the post-PCI showed that there was a remarkable improvement in the left ventricular systolic performance. This was seen by an increase in mean LVEF of 44.6% to 50.8% (p < 0.001), accompanied by significant decreases in LVEDV and LVESV, which was a positive sign of ventricular remodeling. The results of the procedures were of high quality, and the number of complications was low, due to which there were no in-hospital deaths.Conclusion: The use of PCI in CTO patients is linked with the substantial improvement of echocardiographic variables, especially the elevated LVEF and decreased ventricular volumes. The results assist in the support of PCI as a strong therapeutic solution in enhancing cardiac functions and reverse remodeling in patients with different levels of baseline ventricular dysfunction.